Two Novelties in Ion-pair Formation-based Potentiometric Titrations of Anionic Surfactants - Mikysek, Tomáš; Stočes, Matěj; Vytřas, Karel (My University, 2016)
Two novel approaches in ion-pair formationbased potentiometric titrations of anionic surfactants are presented. First, a new type of the low ohmic coated-wire ion-selective electrode is introduced; the polymeric membrane containing a plasticizer mixed with carbon powder. Second, didecyldimethylammonium chloride as the cationic titrant is for the first time proposed and applied, providing the titration curves with the highest potential jump.
Nový příspěvek kpotenciometrickým titracím aniontových tenzidů
Keywords: Surfactants; Potentiometric Titration; Ion-Selective Electrodes; tenzidy; potenciometrické titrace; iontově-selektivní elektrody